2003
DOI: 10.1128/jvi.77.17.9522-9532.2003
|View full text |Cite
|
Sign up to set email alerts
|

Newcastle Disease Virus V Protein Is a Determinant of Host Range Restriction

Abstract: ). We now show that the NDV V protein plays an important role in host range restriction. In order to study V functions in vivo, recombinant NDV (rNDV) mutants, defective in the expression of the V protein, were generated. These rNDV mutants grow poorly in both embryonated chicken eggs and chicken embryo fibroblasts (CEFs) compared to the wild-type (wt) rNDV. However, insertion of the NS1 gene of influenza virus A/PR8/34 into the NDV V(؊) genome [rNDV V(؊)/NS1] restores impaired growth to wt levels in embryonat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
231
1
4

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(238 citation statements)
references
References 38 publications
(42 reference statements)
2
231
1
4
Order By: Relevance
“…Differences between avian and primate cells with regard to sialic acid receptors for viral attachment comprise one possible factor in the host range restriction. It also might be that NDV is less able to block the type I IFN response in primate cells, as suggested by previous studies (40). In the case of the host range restriction of bovine parainfluenza virus type 3 in primates, each gene appeared to make a contribution (41).…”
Section: Discussionmentioning
confidence: 61%
“…Differences between avian and primate cells with regard to sialic acid receptors for viral attachment comprise one possible factor in the host range restriction. It also might be that NDV is less able to block the type I IFN response in primate cells, as suggested by previous studies (40). In the case of the host range restriction of bovine parainfluenza virus type 3 in primates, each gene appeared to make a contribution (41).…”
Section: Discussionmentioning
confidence: 61%
“…The phenotype of rSeV⌬V is very similar to that of rSV5V⌬C (i.e., increased CPE in culture and attenuated in vivo), suggesting that SeV V protein might have a function similar to that of SV5 V protein in preventing cell death. Recently, a recombinant NDV lacking its V gene (rNDV⌬V) has been recovered that induces increased apoptosis in CEF cells, suggesting that NDV V has an anti-apoptosis function (38). The mechanism by which V protein blocks virus-induced apoptosis is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…17 NDV, an avian virus, may represent a different example of oncolytic virus as its V gene product, that is known to counteract IFN response in avian cells, is completely inactive in mammalian cells. 39 Notwithstanding, the oncolytic effect of NDV was shown related to a deficient IFN system in one study 15 and conversely shown independent of the IFN system in yet another study. 19 To further investigate the role of the IFN system in the oncolytic mechanism of NDV-HUJ, we pretreated the cells with recombinant IFN-b and tested for replication and the oncolytic activities of the virus.…”
Section: Discussionmentioning
confidence: 97%